Analytics in a big data world : the essential guide to data science and its applications - Baesens, Bart. (Hoboken, New Jersey : Wiley, 2014)
The guide to targeting and leveraging business opportunities using big data & analytics By leveraging big data & analytics, businesses create the potential to better understand, manage, and strategically exploiting the complex dynamics of customer behavior. Analytics in a Big Data World reveals how to tap into the powerful tool of data analytics to create a strategic advantage and identify new business opportunities. Designed to be an accessible resource, this essential book does not include exhaustive coverage of all analytical techniques, instead focusing on analytics techniques that really...
Big Data and Analytics -- Data Collection, Sampling, and Preprocessing -- Predictive Analytics -- Descriptive Analytics -- Survival Analysis -- Social Network Analytics -- Analytics: Putting It All to Work -- Example Applications.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Big data; Management -- Statistical methods; Management -- Data processing; Decision making -- Data processing; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Big data; Decision making -- Data processing; Management -- Data processing; Management -- Statistical methods; Electronic books; Electronic books